Development of dialysis disequilibrium‐like clinical signs during postobstructive management of feline urethral obstruction. (15th July 2014) - Ostroski, Cassandra J.; Cooper, Edward S.
Abstract Objective To describe the clinical features, treatment, and outcome of a cat with acute neurologic signs subsequent to relief of urethral obstruction and rapid resolution of severe azotemia, suggesting a process similar to dialysis disequilibrium syndrome. Case Summary A male castrated domestic short‐hair cat was presented for weakness and dull mentation. Initial physical examination was consistent with urethral obstruction and laboratory data demonstrated severe azotemia, hyperkalemia, and acidemia. Interventions for hyperkalemia and urethral catheterization were performed without complication. The patient demonstrated a marked postobstructive diuresis and 7 hours after presentation suffered a grand mal seizure and was neurologically inappropriate. These changes corresponded with marked decreases in blood urea nitrogen (from 89.25 mmol/L to 19.99 mmol/L [250 mg/dL to 56 mg/dL]) and calculated serum osmolality (429 mOsm/kg to 359 mOsm/kg) from initial presentation without other apparent cause for seizure activity. The patient was treated with hypertonic saline (bolus and continuous infusion) for presumed osmotic injury (dialysis disequilibrium‐like clinical signs) along with other supportive care. All neurologic signs resolved within 48 hours, the urinary catheter was removed, and the patient was discharged after 24 hours of observation of spontaneous urination. New or Unique Information Provided Dialysis disequilibrium syndrome has been documented in small animals, but similar signs have not been reported as a sequelae of treatment of feline urethral obstruction. Urethral obstruction is a common emergency and practitioners should be aware of this potential complication as a cause of delayed neurologic recovery or seizures in the postobstructive period.